Heparin-induced thrombocytopenia: The role of platelets genetic polymorphisms. (August 2013) - Pamela, Scarparo; Anna Maria, Lombardi; Elena, Duner; Giovanni, Malerba; Emanuele, Allemand; Silvia, Vettore; Carmen, Blumentritt; Andreas, Greinacher; Fabrizio, Fabris
<x xml:space="preserve">Abstract</x> Heparin-induced thrombocytopenia (HIT) is a severe complication of heparin therapy, characterized by thrombocytopenia and an increased risk for thrombotic complications secondary to the formation of IgG antibodies (Ab), recognizing a complex of heparin (H) and PF4. Using the 4T clinical score for HIT and the presence of heparin-associated Ab assayed by enzyme-linked immunosorbent assay and heparin-induced platelet aggregation, we define the phenotype of three groups of patients: 51 H/PF4/Ab patients with antibodies and without thrombocytopenia; 50 patients with thrombocytopenia (HIT) and 53 patients with thrombosis (HITT). In these patients we studied four polymorphisms: FcγRIIA-H131R, GpIIb/IIIa-HP-1, PECAM1-L125V (in linkage-disequilibrium with S563N and R670G), and FcγRIIIA-F158V, to understand if these variations may influence the different phenotypes of the patients. There were no difference in genotype or allele frequencies between controls and the three groups of patients. Afterward, we created a genotype score for multiple risk alleles for thrombosis considering as risk genotype FcγRIIA R/R131, HPA-1a/b, and PECAM1-V/V125. These polymorphisms were overrepresented in HITT patients, ascertained by a permutation test (10 000 replicates) p = 0.0198 for the two-single-nucleotide polymorphism (SNP) model and p = 0.0119 for the three-SNP model. The calculated odds ratio for thrombosis was 4.01[CI: 2.30–6.96] in the case of the presence of two at risk genotypes and 8.002 [CI: 4.59–13.93] if all the three at risk genotypes were present. In conclusion these polymorphisms could contribute to the risk of thrombotic complications in HIT.